Analisis Standar Laboratorium Pendidikan Fisika dalam Meningkatkan Hasil Praktikum Mahasiswa di Universitas Jabal Ghafur - Maulani Maulani; Afriza Afriza; Aida Rahmy; Muksalmina Muksalmina; Mulia Rahmi (Universitas Negeri Medan, 2025)
Physics laboratories play a crucial role in supporting the practicum activities of physics education students. This study aims to analyzethe standards of the physics laboratory at Jabal Ghafur University and their impact on the quality of students practicum. The research used a qualitativeapproach with the CIPP (context, input, process, product) evaluation model. Data were collected throughobservation, interviews, questionnaires, and documentation, with a sample of fifth-semester students actively involved in practicum. The results indicate that theoverall laboratory management is in the adequate category, with an average score of 2.15 and a satisfaction rate of 53.7%. The readiness of laboratory asistants/lecturers scored the highest, while the adequacy of laboratory standars received the lowest score. The study concludes that although the laboratory meets minimum satndars, comprehensive improvements are still needed, particularly in facilities and the effectiveness of practicum activities to support student learning outcomes.